2012
DOI: 10.1063/1.4765033
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the formation of ultrafine spinel CoFe2O4 nanoplatelets and their magnetic properties

Abstract: Cobalt ferrite (CoFe 2 O 4 , CFO) nanoplatelets with a rhomboidal shape were synthesized through a facile hydrothermal route using a very low concentration precursor at low temperatures. The effects of reaction temperature and time on the morphologies as well as the sizes of the products were systemically investigated. The as-synthesized CFO nanocrystals showed a special rhomboidal shape with crystal growth along the (111) direction. The very low concentration precursor plays an important role in forming CFO n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 55 publications
1
15
0
3
Order By: Relevance
“…The low-frequency mode at 482 cm −1 is assigned as the vibrations of the octahedral sublattice, whereas the high energy phonon mode at 701 cm −1 originates from vibrations of the tetrahedral sublattice. 27 The …”
Section: A X-ray Diffraction Study (Xrd)mentioning
confidence: 99%
“…The low-frequency mode at 482 cm −1 is assigned as the vibrations of the octahedral sublattice, whereas the high energy phonon mode at 701 cm −1 originates from vibrations of the tetrahedral sublattice. 27 The …”
Section: A X-ray Diffraction Study (Xrd)mentioning
confidence: 99%
“…The results demonstrate a good single-phase magnetic behavior, and the magnetization changes smoothly with the applied field, which suggest that the soft and hard magnetic phase exchange coupled strongly [8,25].
Figure 5 Magnetic hysteresis loops and tendency of M s and H c of the samples.
…”
Section: Resultsmentioning
confidence: 93%
“…Recently, a number of studies about the synthesis of CoFe 2 O 4 have been reported. CoFe 2 O 4 nanoparticles were fabricated by a sol-gel method by Xi et al [5], Mazario fabricated the CoFe 2 O 4 ferrite nanoparticles by an electrochemical method [6], CoFe 2 O 4 nanofibers was obtained by the electrospinning in 2009 [7], Liu et al prepared the CoFe 2 O 4 nanoplatelets using a facile hydrothermal route [8], and so on. However, the applications of CoFe 2 O 4 are often limited by its relatively low coercivity ( H c ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to notice that the Raman modes of the NiFe 2 O 4 nanoparticles annealed at lower temperature 200 o C are very broad and shift to low frequency as compared to that of nanoparticles annealed at higher temperature. This feature is related to a consequence of phonon confinement effect in nanocrystals [42][43].…”
Section: Field-emission Scanning Electron Microscopymentioning
confidence: 97%